Brain structural connectivity, anhedonia, and phenotypes of major depressive disorder: A structural equation model approach. Issue 15 (24th July 2021) - Pfarr, Julia‐Katharina; Brosch, Katharina; Meller, Tina; Ringwald, Kai Gustav; Schmitt, Simon; Stein, Frederike; Meinert, Susanne; Grotegerd, Dominik; Thiel, Katharina; Lemke, Hannah; Winter, Alexandra; Waltemate, Lena; et al.
Abstract: Aberrant brain structural connectivity in major depressive disorder (MDD) has been repeatedly reported, yet many previous studies lack integration of different features of MDD with structural connectivity in multivariate modeling approaches. In n = 595 MDD patients, we used structural equation modeling (SEM) to test the intercorrelations between anhedonia, anxiety, neuroticism, and cognitive control in one comprehensive model. We then separately analyzed diffusion tensor imaging (DTI) connectivity measures in association with those clinical variables, and finally integrated brain connectivity associations, clinical/cognitive variables into a multivariate SEM. We first confirmed our clinical/cognitive SEM. DTI analyses (FWE‐corrected) showed a positive correlation of anhedonia with fractional anisotropy (FA) in the right anterior thalamic radiation (ATR) and forceps minor/corpus callosum, while neuroticism was negatively correlated with axial diffusivity (AD) in the left uncinate fasciculus (UF) and inferior fronto‐occipital fasciculus (IFOF). An extended SEM confirmed the associations of ATR FA with anhedonia and UF/IFOF AD with neuroticism impacting on cognitive control. Our findings provide evidence for a differential impact of state and trait variables of MDD on brain connectivity and cognition. The multivariate approach shows feasibility of explaining heterogeneity within MDD and tracks this to specific brain circuits, thus adding to better understanding of heterogeneity on the biological level. Abstract : In this article, we analyzed a large cohort of n = 595 major depressive disorder (MDD) patients using structural equation modeling of brain connectivity, clinical, and cognitive parameters to identify the relation of anhedonia, neuroticism, and state anxiety as well as cognitive control. Results show a brain structural overlap of anhedonia and cognitive control as well as of neuroticism and cognitive control, contributing to disconnection in MDD.